Application of computational modeling to the kinetics of precipitation of aluminum nitride in steels - e Silva Costa A.; Nakamura L.; Rizzo F. (Journal of Mining and Metallurgy. Section B: Metallurgy)
In previous works the possibilities and limitations of the application of calculations in the Al-Fe-N system to describe the precipitation of AlN in steel, both in the solid state and during the solidification were discussed and some difficulties related to the extension of these calculations to more complex steel systems, due to limitations in the thermodynamic data were also presented. Presently, the precipitation kinetics of AlN in ferrite (BCC) and austenite (FCC) is discussed. The correct description of the precipitation of AlN in both phases is relevant to: (a) the precipitation at higher temperatures, in the austenite field, that occurs in some steels, (b) the concurrent precipitation of this nitride with the annealing treatment, when the steel is mostly ferritic, used in the processing of some types of deep drawing steels (c) the precipitation of this nitride in some silicon alloyed electric steels at relatively high temperatures, when these steels can have significant fractions of BCC and FCC in their microstructure. The precise knowledge of the precipitation-dissolution behavior of AlN in special in these two latter classes of steels is of great importance to their correct processing. In this work, a computational tool for simulating multiparticle precipitation kinetics of diffusion-controlled processes in multi-component and multi-phase alloy systems is employed in an attempt to describe these precipitation processes. The results are compared with experimental data on precipitation. The assumptions necessary for the application of the multi-particle modeling tool are discussed, agreements and discrepancies are identified and some possible reasons for these are indicated. Furthermore, the impact of the use of different sources of data on steel processing development is discussed and the need for further studies highlighted.